Photooxidation of vulcanized EPDM/montmorillonite nanocomposites - Morlat-Therias, Sandrine; Fanton, Elisabeth; Tomer, Namrata S.; Rana, Sravendra; Singh, R. P.; Gardette, Jean Luc (Polymer Degradation and Stability, 2006)
The photooxidation of a vulcanized ethylene-propylene-diene monomer (EPDM)/montmorillonite nanocomposite as well as EPDM/nanocomposite with stabilizers was studied under accelerated UV-light irradiation (lambda >= 300 nm, 60 degrees C) for different times. The development of functional groups during oxidation was monitored by infrared spectroscopy. Photodegradation of the neat polymer and composites took place and the increases of absorbance in hydroxyl and carbonyl groups with irradiation times and also the decreases of the EPDM unsaturations were measured. The data indicated that the photooxidation products were not changed in the presence of the nanofiller. However, the presence of MMt was observed to dramatically enhance the rate of photooxidation of EPDM with a shortening of the oxidation induction time, leading to a decrease of the durability of the nanocomposites. On the other hand, it was observed that addition of stabilizers, either Tinuvin P or 2-mercaptobenzimidazole, was efficient in inhibiting the degradative effect of MMt. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EPDM; Nanocomposite; photooxidation rate; stabilization

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Photodegradation of ethylene/propylene/polar monomers, Co-, and terpolymers. II. prepared by Ni catalyst systems - Fernandes, Susete N.; Correia, Sandra; Matos, Ines; Marques, Maria M.; Rana, Sravendra; Kumar, Bijandra; Gupta, M. K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
The copolymers of ethylene/propylene as well as their terpolymers with polar monomers were prepared by Ni-catalyst systems and their photodegradation behavior was studied by Fourier transform infrared spectroscopy. The polar monomers used to synthesize co- and terpolymers of ethylene/propylene/polar monomer were 5-hexen-1-ol, 10-undecen-1-ol, acrylamide, methylmethacrylate, acrylonitrile, and methylvinyl ketone. The morphological changes of the irradiated samples were determined by scanning electron microscopy. The photodegradation kinetics has also been studied. The surface damage caused by polychromatic irradiation (lambda >= 290 nm) at 55 degrees C in atmospheric air is presented in different micrographs. The rate of photo-oxidative degradation is very fast in terpolymers containing polar monomers as compared with copolymers and homopolymers. The morphological study of the photodegraded samples showed a very good correlation with the photodegraded results. (c) 2007 Wiley Periodicals, Inc.
Keywords: copolymerization; Ethylene; Photodegradation; polar monomers; propylene

Synthesis and characterization of hindered amine light stabilizers based on end functionalization of polypropylene - Reddy, K. Raghunatha; Kumar, Bijendra; Rana, Sravendra; Tevtia, Amit K.; Singh, R. P. (Journal of Applied Polymer Science, 2007)
A polymeric hindered amine light stabilizer (HALS), where HALS moiety was attached at the terminal end of the polypropylene chain via end-functionalized vinylidine PP through simple organic reactions, was synthesized. It comprises the synthesis of vinylidine-terminated polypropylene by using Cp2ZrCl2/MAO as catalyst system and epoxidation of vinylidene polypropylene. The final product was synthesized by carrying out the reaction between epoxy end functionalized polypropylene and 4-amino-2,2,6,6-tetrametyl piperidine. The final product was characterized by using H-1 NMR, C-13 NMR, and FT-IR spectra. Functionality was calculated by using vapor phase osmometry and H-1 NMR. The solubility and diffusion coefficient of the product were calculated and also its stabilization performance was checked. (c) 2007 Wiley Periodicals, Inc.
Keywords: end functionalization; functionalization of polymers; polymeric HALS; polypropylene; vinylidine and photostabilization

Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS

Functionalization of single-walled carbon nanotubes with azides derived from amino acids using click chemistry - Kumar, Indresh; Rana, Sravendra; Rode, Chandrashakher V.; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2008)
Single-walled carbon nanotubes (SWCNTs) were chemically functionalized with amino acid-based moieties. The covalent functionalization of alkyne-derived SWCNTs with well defined azides derived from amino acids was accomplished through Cu(I)-catalyzed Huisgen [3+2] dipolar cycloaddition click chemistry. Transmission electron microscopy, Raman spectroscopy, and infrared spectroscopic measurements confirmed the functionalization of SWCNTs by organic molecules derived from amino acids, and the resulting material showed some good solubility in the organic solvents such as tetrahydrofuran, CH2Cl2, and CHCl3.
Keywords: Amino acids; Carbon nanotubes; Click chemistry; Functionalization

Assembly of gold nanoparticles on single-walled carbon nanotubes by using click chemistry - Rana, Sravendra; Kumar, Indresh; Yoo, Hye Jin; Cho, Jae Whan (Journal of Nanoscience and Nanotechnology, 2009)
Azide moiety-functionalized gold nanoparticles were conjugated with acetylene functionalized single-walled carbon nanotubes by employing copper-catalyzed Huisgen's [3+2] dipolar cycloaddition `click chemistry' reaction. Evidences of conjunction were observed by TEM, EDX and Raman images.
Keywords: Carbon nanotubes; Click chemistry; Functionalization; Nanoparticles

Synthesis and characterization of polyurethane-grafted single-walled carbon nanotubes via click chemistry - Rana, Sravendra; Cho, Jae Whan; Kumar, Indresh (Journal of Nanoscience and Nanotechnology, 2010)
Polyurethane (PU)-grafted carbon nanotubes were synthesized by the coupling of alkyne moiety decorated single walled carbon nanotube (SWCNT) with azide moiety containing PU using Cu(I) catalyzed Huisgen [3 + 2] cycloaddition click chemistry. The azide moiety containing poly(E-caprolactone)diol was synthesized by ring-opening polymerization and further used for PU synthesis. Alkyne-functionalizion of SWCNT was completed by the reaction of p-aminophenyl propargyl ether with SWCNT using a solvent free diazotization procedure. Nuclear magnetic resonance, Fourier transform infrared, and Raman spectroscopic measurements confirmed the functionalization of SWCNT. Scanning electron microscopy and transmission electron microscopy images showed an excellent dispersion of SWCNTs, and specially debundling of SWCNTs could be observed due to polymer assisted dispersion. A quantitative grafting was successfully achieved even at high content of functional groups.
Keywords: Carbon nanotubes; Click chemistry; dispersion; polyurethane

Synthesis of hybrid 1,2,3-triazolo-delta-lactams/lactones using Huisgen [3+2] cycloaddition `click-chemistry' in water - Kumar, Indresh; Rana, Sravendra; Cho, Jae Whan; Rode, Chandrashekhar V. (Tetrahedron-Asymmetry, 2010)
The synthesis of a new class of hybrid 1,2,3-triazozlo-delta-lactams/lactones has been achieved using the Huisgen [3+2] dipolar cycloaddition `click-chemistry' reaction of various organic azides with an activated alkyne in water, followed by cyclization. (C) 2010 Elsevier Ltd. All rights reserved.